EDITORIAL - Mariano, A. B. (Revista de Engenharia Térmica, 2015)
The need for diversification of the global energy grid is present in the speeches of most governments, the motivation of scientists and the perception of a growing segment of the population. Even so, the dependence on non-renewable fuels, such as fossil fuels, has been increasing progressively due to the rapid global growth, rising consumption and increasing purchasing power of the population. Besides searching global solutions to resolve the energy quest, efforts must be directed to short-term actions, taking advantage of the available scientific and technological knowledge to improve the performance of existing systems and in use today. Improving the efficiency of cooling systems, which are responsible for much of the world electricity consumption through intelligent control of compressors can reduce up to 50% electricity consumption, and thus provide economic and strategic advantages to countries that encourage this type of initiative. Likewise, the reduction of electricity for domestic heating or showering can be obtained by waste heat recovery, solar heating or the use of heat pumps with immersed condensers, among others, contributing to the reduction of electric energy consumption. A challenge to be overcome is the popularization of such technologies in the form of final product at affordable costs. Also, for popular use, it is the important the interest of nation leaders in order to drive the use of those technologies through tax incentives and public policies. Other advances could be achieved by the use and improvement of biotechnological processes, coupling the treatment of emissions and effluents to the production of biofuels, as well as high aggregated value products. Through exergy analysis, thermoeconomics, mathematical modeling, simulation and optimization, thermal engineering is able to contribute to the efficient coupling of such different biotechnological processes and contribute to decreasing dependence on fossil fuels.